Ethical and Islamic-Based Digital Marketing: The Role of Instagram in Promoting Happy Hive Malaysia School - Dira Mastika Purba; Alfi Amalia (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
he development of digital technology has encouraged educational institutions to utilize social media as a medium for institutional communication and promotion. Instagram has become one of the most widely used platforms due to its visual characteristics, which allow educational information to be presented attractively while enabling interaction between schools and the community. This study aims to analyze the implementation of digital marketing through Instagram at Happy Hive Playschool & Preschool Malaysia, examine the role of the platform in supporting school promotion, and evaluate the alignment of promotional content with the principles of Islamic marketing ethics. This research employs a descriptive qualitative approach. Data were collected through observation of the school’s Instagram activities, in-depth interviews with the social media administrator, and documentation of digital promotional content. The data were analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The findings show that Instagram is actively used as a promotional and institutional communication medium. The content is largely educational, highlighting learning activities, early childhood development, and school programs. These publications contribute to increasing institutional visibility and strengthening public trust. From the perspective of Islamic marketing ethics, the promotional content reflects honesty, trustworthiness, and fairness while avoiding manipulative practices.